The Habitat Characteristics of Red Shrimp (Parhippolyte uveae) in Swamp Waters Around the Koguna Beach Area, Buton Regency, Southeast Sulawesi: Karakteristik Habitat Udang Merah (Parhippolyte uveae) di Perairan Rawa Sekitar Kawasan Pantai Koguna Kabupaten Buton, Sulawesi Tenggara - Muhammad Farhan Pratama; La Sara La Sara; Halili Halili; Muhammad Nur Findra (Department of Aquatic Resources Management, Faculty of Fisheries and Marine Science, IPB University, 2023)
Around the Koguna Beach area, which is ± 157 meters from the coastline, there is a closed water like a swamp. These waters are brackish and inhabited by red shrimp (Parhippolyte uveae). The purpose of this study was to determine the characteristics of the shrimp habitat. This research was conducted in November–December 2021 in Mopaano Village, Lasalimu Selatan District, Buton Regency. The research location was deliberately set in 2 zones with different habitat characteristics. The results showed that in Zone 1 red shrimp were found with a high relative abundance which indicated that the zone was favored by red shrimp. Habitat in this zone has characteristics in the form of rocks and mangrove roots, higher density of mangrove canopy cover, as well as parameters of the aquatic environment that are suitable for the life of red shrimp. This habitat is anchialine waters which are still influenced by the tides from the sea but are not directly connected to the surface.